The Role of Big Business in the Development of Territories (Illustrated by Steel-Making Corporations of Russia) - M. K. Malyshev (Вестник Российского экономического университета имени Г. В. Плеханова)
The author tries to investigate the role of ferrous metallurgy in the regional development. From 2012 to 2019 steelmaking works of the Vologda region (‘Severstal’), Chelyabinsk region (‘MMK’) and Lipetsk region (‘NLMK’) increased the volume of steel production by 12.1, 1.8 and 5.3%, respectively. These enterprises play a dominant role in shaping profit tax in these regions, especially ‘NLMK’, whose average specific weigh of the profit tax in its total amount in the Lipetsk region made up 57.9%. Analysis of steel-making works’ settlements with the budget system of the Russian Federation showed a growth in tax receipts both to the budget of the region and to the federal budget. It can be explained by the fact that besides a twofold rise in earnings is a serious amount of profit before taxation obtained by the company within the period from 2016 to 2019. These steel-making works provide jobs for more than 100,000 people. All these companies are socially responsible, which includes such goals as health protection and creation of comfortable conditions for workers, safeguarding ecological situation in the region and resource-saving, participation in social projects, such as construction of sport facilities, financing of cultural and educational events. Key findings of the research could be useful for decision-makers in the field of effective interaction of big business and bodies of power.